The changing scope of religious authority and reconfigurations of social status in post-socialist Russia. Issue 2 (3rd April 2018) - Ładykowska, Agata
ABSTRACT: As the Russian Orthodox Church (ROC) advocates the need to educate its believers in spiritual and moral matters, there is also a will to encourage people to attend adult Sunday schools. These schools are typically run by professional secular teachers, usually Soviet-trained middle-aged women. Due to their elevated role in creating a new Soviet man and woman and consequential social respect that they gained, these teachers became iconic figures of authority for generations of Russians, a quality which endures despite the loss of social prestige in an era of market capitalism. The post-Soviet church offers new opportunities for teachers to regain authority, status and respect in the ROC's Sunday schools. In that capacity, they exercise significant influence in shaping how the church's moral doctrines are received.